Cytotoxic and antigenotoxic properties of phenolic compound isolated from the fruit of Terminalia chebula on HeLa cell - K. Soumya; Jesna James; T. M. Archana; A. T. Dhanya; A. P. Shahid; S. Sudheesh (Beni-Suef University Journal of Basic and Applied Sciences, 2019)
Abstract Background DNA in a human cell is subjected to constant assault from both environmental factors and normal metabolic processes. Accumulation of DNA damage drives the progression of many health disorders like aging, cancer, diabetes, and neurodegenerative disorders. Results The present study focuses on the isolation of phenolic compound from the fruit of Terminalia chebula and its protective role on induced DNA damage. Diethyl ether and ethyl acetate extract of Terminalia chebula fruit were subjected to column chromatographic purification, and the fractions obtained were tested for the presence of phenolics. Fraction-12 isolated from diethyl ether extract was identified as gallic acid, which is used for cytotoxic and DNA damage protection activity assays. To select a non-toxic concentration of isolated compound, cytotoxicity was assessed by MTT assay. Gallic acid showed moderate toxicity at the highest concentration tested (i.e., percentage cell viability at 100 μg/ml is 40.51 ± 1.31). Antigenotoxic effect of gallic acid on HeLa cells was carried by alkaline comet assay. The compound showed significant protective abilities against hydrogen peroxide-induced DNA damage in HeLa cells. Conclusion These results show the importance of gallic acid isolated from Terminalia chebula fruit, as protector of oxidative stress-induced DNA damage.